How Children Feel Matters: Teacher–Student Relationship as an Indirect Role Between Interpersonal Trust and Social Adjustment - Dong, Yan; Wang, Hongfei; Luan, Fang; Li, Zheneng; Cheng, Li (Frontiers in Psychology, 2021)
Previous studies have demonstrated positive correlations between children’s interpersonal trust and social adjustment. However, the psychological mechanism underlying this effect is still unclear. The current study tested the indirect roles of teacher–student relationships from both students’ and teachers’ perspectives between them in the Chinese context. In total, 709 pupils from grade 3 to grade 5, and their 17 head teachers from a Chinese public primary school participated in this study. Children’s Generalized Trust Beliefs Scale, Social Adjustment Scale for Children and Adolescents, and Teacher–Student Relationship Questionnaire were used in this study. All these variables were correlated with each other. Structural equation models showed that the interpersonal trust indirectly influenced social adjustment through the teacher–student relationship from students’ perspective, while the teacher–student relationship from teachers’ perspective did not play an indirect role. These findings suggest that the teacher–student relationship perceived by students is more important for children’s social adjustment than that perceived by teachers. Both parents and teachers should pay more attention to developing children’s interpersonal trust, build better teacher–student relationships, and focus more on how children feel about the relationship.